2020
DOI: 10.1016/j.jaccas.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

“Back to the Future” for STEMI?

Abstract: Central Illustration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…21,22 There were remarkable reductions in STEMI activations worldwide with substantial decrease in use of coronary angiography and PCI, longer door-toballoon and total ischemic times, and increased risk of mechanical complications. [21][22][23][24][25][26] In parallel, we observed a remarkable increase in In parallel with previous observations, 10,11 we found that late presenters were more likely to be older, female, and have a high cardiovascular risk profile. It is likely that atypical ischemic symptoms, known to be common in these patients, may delay seeking care.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…21,22 There were remarkable reductions in STEMI activations worldwide with substantial decrease in use of coronary angiography and PCI, longer door-toballoon and total ischemic times, and increased risk of mechanical complications. [21][22][23][24][25][26] In parallel, we observed a remarkable increase in In parallel with previous observations, 10,11 we found that late presenters were more likely to be older, female, and have a high cardiovascular risk profile. It is likely that atypical ischemic symptoms, known to be common in these patients, may delay seeking care.…”
Section: Methodssupporting
confidence: 87%
“…National and local actions to mitigate the pandemic, such as lockdown restrictions, social isolation with substantial fear of infection, and deferral of routine health care, subsequently resulted in unintended consequences in STEMI care 21,22 . There were remarkable reductions in STEMI activations worldwide with substantial decrease in use of coronary angiography and PCI, longer door‐to‐balloon and total ischemic times, and increased risk of mechanical complications 21–26 . In parallel, we observed a remarkable increase in late presenters (almost doubled) during the early phase of the Covid‐19 pandemic in 2020.…”
Section: Discussionmentioning
confidence: 74%
“…Another important limitation is the lack of pre-hospital data regarding total ischemic and transfer times for patients presenting to a non-PPCI hospital. Late STEMI presentations have been reported during the pandemic ( 19 , 20 ). In many patients, D2B time could not be accurately estimated because of atypical presentations (i.e., dyspnea instead of chest pain) that could not be timed to STEMI onset per se in the setting of COVID 19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Since the mortality of untreated MI approximates 30–40% [ 16 ] and as 70% of the French territory was, similar to “Pays-de-la-Loire” province, relatively spared by COVID-19 (Supplemental figure), the observation that the number of missing MIs represented nearly 40% of the COVID-related deaths in that province may raise fears of a very heavy nationwide MI-related death toll. Further studies will be needed to detect a potential resurgence of mechanical complications or heart failure [ 17 , 18 ] and increase of cardio-vascular mortality as a consequence of COVID-19 outbreak-related lockdown.…”
Section: Discussionmentioning
confidence: 99%